The effect of titanium oxide and hydroxyapatite on the mechanical properties of wollastonite - Ragurajan D.; Satgunam M.; Golieskardi M.; Sankar U.; Ng A.M.H. (Cogent OA, 2023)
The effect of incorporation of titanium oxide (TiO2) and hydroxyapatite (HA) on the mechanical properties of wollastonite (CaSiO3) was investigated in this study. TiO2/CaSiO3/HA composites were prepared and characterized by means of physical and mechanical properties. Morphology analysis revealed that the wollastonite composite possesses a rough surface. Moreover, the addition of TiO2 and HA to wollastonite was evaluated by means of bulk density and Vickers Hardness. The wollastonite composites containing TiO2 (1030 wt%) and HA (2040 wt%) were sintered between 1230C and 1270C, with a ramp rate of 10C/min and a holding time of 2 h. The results indicated that the additives played a significant part in enhancing the physical and mechanical properties of the composite wollastonite in comparison to the pure wollastonite, particularly in composites containing higher percentage of TiO2 (2530 wt%) and lower HA (2025 wt%). Furthermore, the results obtained from the XRD analysis revealed that the newly formed apatite particles on the surface of the wollastonite composite were comprise of superfine crystalline and/or defective structure grains. 2019, 2019 The Author(s). This open access article is distributed under a Creative Commons Attribution (CC-BY) 4.0 license.